Investigation of Adaptive Beam-forming Algorithms for Smart Antennas System. Issue 1 (January 2021) - Kaur, Simrandeep; Kumar, Naresh; Dubey, Subhash
Abstract: Smart antennas are examined as a promising technology in wireless communication systems. In the development of smart antenna technology, Adaptive beam-forming is the most important aspect. Adaptive beam-forming uses various algorithms to identify the signals in the desired direction and separate the interference from the undesired/unwanted direction. In this paper, Proposed Adaptive Beam-forming Algorithm offers the better solution for reducing interference and improves the system capacity. The main objective of this paper is to analyze the different approaches used for designing the smart antennas to track the desired signal and put perfect null towards the interferer signal.